Digital Competitiveness of European Union Member States from the Perspective of Human Capital (European Journal of Formal Sciences and Engineering, 2019)
The concepts of "digital skills" and "digital competences" are key terms in the discussion related to the type of skills people need nowadays not only in terms of digital inclusion in the society but also in terms of employability. According to the latest definition by the European Union, digital skills “can be broadly understood as the ability to locate, organise, understand, evaluate, create and share information using digital technology, at different levels of competence” CITATION Eur171 ł 1033 (European Commission, 2017). The rapid development of information and communication technologies (ICT) bring major transformations with respect to the individual’s integration in society and employability. The paper analyses the 28 member states of the European Union (EU) from the perspective of the pesons’ digital skills and employability in the science, technology (including the ICT) sectors over the period 2015 - 2017. The paper covers the following areas of research: (1) Overall digital skills, computer skills, internet skills of individuals in the EU 28; (2) Human capital with advanced and specialist digital skills in ICTin the EU 28; (3) Evolution of the digital competitiveness of the EU 28 member states from the perspective of human capital over the period 2015-2017. Quantitative and qualitative research methods were employed for data collection and analysis: database research and analysis; statistical analysis; content and thematic research and analysis from policy papers and reports.
Keywords: digital economy; digital society; digital skills; information and communication technologies